Illegal Immigration (Case Study of the Missing Ship of Alexandria 2014) - Hejazi , Heba Ziad; El- Mougher, Mohammed M.; El- Agha, Mohamed R. (Journal of Risk and Crisis Management, 2019)
This study aims to shed lights on the illegal immigration of individuals outside their lands. It explains the definition and the size of this illegal phenomenon. As you know that there are a lot of sinking ships. This case is repeated frequently specially after the Israeli military aggression in 2004.All of this happens because of a huge number of factors such as economic, social, and political.These reasons create the suitable environment for immigration.This study clarifies some of this phenomenon which is spread recently.The researcher used the descriptive methods and various tools of reports and interviews.The study shows different results, the most important one is the large proportion of Palestinian emigrants especially the young and the holders of educational qualifications.This means that we face a real problem which wastes energies and affects the construction and development of our society.It affects the health, security and psychological of human beings. So, we must fight this bad phenomenon and work on empowering the young and exploiting their potentials.As you know that the young are the most important part in any society to achieve real development in short and long term. As you know that the young are the most important part in any society to achieve real development in short and long term.Finally, the study recommends reduce this phenomenon by appropriate strategies, radical solutions, and awareness of individuals.
Keywords: migration; death Ships; poverty; risk